Are low maternal estriol levels a predictor for pro‐opiomelanocortin (POMC) deficiency caused by POMC mutation during pregnancy?. (12th September 2013) - Aldemir, Ozgur; Ozen, Samim; Sanlialp, Cigdem; Ceylaner, Serdar
ABSTRACT Isolated adrenocorticotropic hormone deficiency is a rare cause of adrenocortical insufficiency, especially in children, and may be an underestimated cause of neonatal death. Low estriol levels are usually correlated with compromised uteroplacental perfusion and associated with fetal death. A 30‐years old woman applied for pregnancy follow‐up. Ultrasonographic evaluation and karyotype of the fetus are normal. Low estriol level 0.34 MoM (% 0.24) was detected in maternal triple screening test. Amniocentesis was performed, and chromosomal disorders, steroid sulfatase deficiency, and Smith–Lemli–Opitz syndrome (SLOS) were excluded with karyotype, fluorescence in situ hybridization (FISH), and molecular analysis of SLOS, respectively. As their first child had pro‐opiomelanocortin (POMC) deficiency, POMC gene analysis was performed from both amniotic fluid and ethylene diamine tetra aceticacid (EDTA) blood sample of affected previous child, and homozygote mutation was detected. Fetus is diagnosed as POMC deficiency. We are presenting this case to discuss possible relationship of low maternal E3 levels and fetal POMC deficiency. © 2013 John Wiley & Sons, Ltd.